2016
DOI: 10.1128/mbio.00952-16
|View full text |Cite
|
Sign up to set email alerts
|

Fast Mechanically Driven Daughter Cell Separation Is Widespread in Actinobacteria

Abstract: Dividing cells of the coccoid Gram-positive bacterium Staphylococcus aureus undergo extremely rapid (millisecond) daughter cell separation (DCS) driven by mechanical crack propagation, a strategy that is very distinct from the gradual, enzymatically driven cell wall remodeling process that has been well described in several rod-shaped model bacteria. To determine if other bacteria, especially those in the same phylum (Firmicutes) or with similar coccoid shapes as S. aureus, might use a similar mechanically dri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
23
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
3
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 22 publications
2
23
0
Order By: Relevance
“…In their pioneering study, Zhou et al 6 linked division of S. aureus to a fracture process and postulated that it might result from stress accumulation and mechanical failure of the cell wall, thereby laying the groundwork for viewing bacterial cell division from the perspective of physical forces 32 . Their observations are reminiscent of the "V-snapping" model of cell division in M. smegmatis 33 ; more recently, additional bacterial species have been identified that also undergo abrupt spatial reorientation during cell division 7 (see Figure 4a). This phenomenon (V-snapping) is consistent with a model in which rapid cleavage of sibling cells is due to progressive circumferential rupture of the connecting cell wall starting from the weakest section around the PCF.…”
mentioning
confidence: 89%
“…In their pioneering study, Zhou et al 6 linked division of S. aureus to a fracture process and postulated that it might result from stress accumulation and mechanical failure of the cell wall, thereby laying the groundwork for viewing bacterial cell division from the perspective of physical forces 32 . Their observations are reminiscent of the "V-snapping" model of cell division in M. smegmatis 33 ; more recently, additional bacterial species have been identified that also undergo abrupt spatial reorientation during cell division 7 (see Figure 4a). This phenomenon (V-snapping) is consistent with a model in which rapid cleavage of sibling cells is due to progressive circumferential rupture of the connecting cell wall starting from the weakest section around the PCF.…”
mentioning
confidence: 89%
“…2C). Following septation, aerial hyphae divide into immature spores via a mechanism described as 'V snapping', which relies on turgor pressure and structural weakening of the PG to drive cell division in milliseconds (Zhou et al, 2016). In immature spore chains, the rodlet layer remained intact as a 20-nm thick sheath ( Fig.…”
Section: Streptomyces the Cell Envelope Undergoes Dramatic Remodelinmentioning
confidence: 99%
“…In addition to growing asymmetrically, mycobacteria also divide asymmetrically and undergo a fast, mechanical v-snapping process of daughter cell separation ( Aldridge et al, 2012 ; Richardson et al, 2016 ; Zhou et al, 2016 ). There is evidence to suggest that sites of asymmetric division are not just established at division, but are inherited from previous generations.…”
Section: The Basis Of Asymmetrymentioning
confidence: 99%